2012
DOI: 10.12693/aphyspola.122.896
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Double Cladding Small Dispersion Photonic Crystal Fiber to Guide Ultrashort Pulse at 800 nm

Abstract: The methods using femtosecond lasers are very popular in the world recently. They are used for dierent research methods. We begin to use a multi-photon autouorescence method for cancer tissue detection. We plan to use this method with special photonic crystal ber optic sensors. We would like to use to this detection femtosecond oscillator for 800 nm region. However, according to our information there is no ber which can provide these femtosecond signals at 800 nm region without dispersion and nonlinear eect. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In our prior work Stawska, Bereś-Pawlik (2012) we showed that it is possible to design double clad fibers with very small dispersion at 800 nm. We analyzed two constructions: one with Ge-doped rods and the other with a hollow core.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior work Stawska, Bereś-Pawlik (2012) we showed that it is possible to design double clad fibers with very small dispersion at 800 nm. We analyzed two constructions: one with Ge-doped rods and the other with a hollow core.…”
Section: Introductionmentioning
confidence: 99%